Romantic Relationship Dynamics of Urban African American Adolescents: Patterns of Monogamy, Commitment, and Trust. (May 2015) - Towner, Senna L.; Dolcini, M. Margaret; Harper, Gary W.
Relationship dynamics develop early in life and are influenced by social environments. STI/HIV prevention programs need to consider romantic relationship dynamics that contribute to sexual health. The aim of this study was to examine monogamous patterns, commitment, and trust in African American adolescent romantic relationships. The authors also focused on the differences in these dynamics between and within gender. The way that such dynamics interplay in romantic relationships has the potential to influence STI/HIV acquisition risk. In-depth interviews were conducted with 28 African American adolescents aged 14 to 21 living in San Francisco. Our results discuss data related to monogamous behaviors, expectations, and values; trust and respect in romantic relationships; commitment to romantic relationships; and outcomes of mismatched relationship expectations. Incorporating gender-specific romantic relationships dynamics can enhance the effectiveness of prevention programs.